PEMETAAN CAKUPAN IMUNISASI MR DAN KASUS CAMPAK RUBELLA DI PROVINSI BALI TAHUN 2019 - Handayani, Ni Made Suweni; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH, 2021)
ABSTRACT The information about MR immunization coverage and measles rubella cases at the Health Department was generally presented in the form of tables and graphs so that it could not be used to see detailed information about measles rubella and MR immunization coverage geographically. This study aimed to describe the distribution of measles rubella and MR immunization coverage geographically in the province of Bali. This type of study is descriptive. The analysis used is descriptive with presenting the map. The results of the study showed that the coverage of the MR immunization campaign in each village in Bali was not evenly distributed and there were still villages that had not reached the target. Several cases are still found after the MR immunization campaign in Bali Province. Distribution of suspected cases of measles were the most found in urban and densely populated areas such as Badung, Klungkung, and Denpasar. While rubella positive cases found in rural areas related to incomplete immunization status. The Health Department can utilize digital maps in the process of decision making to control measles and rubella and increase MR immunization coverage by considering regional aspects, monitoring and evaluating a measles and rubella control program which has been done every year. Keywords : Mapping, Measles Rubella, Immunization